Titanite petrochronology linked to phase equilibrium modelling constrains tectono-thermal events in the Akia Terrane, West Greenland - Kirkland, C.L.; Yakymchuk, C.; Gardiner, N. J.; Szilas, K.; Hollis, J.; Olierook, H.; Steenfelt, A. (Chemical Geology, 2020)
GeoHistory Facility instruments (part of the John de Laeter Centre) were funded via an Australian Geophysical Observing System (AGOS) grant provided to AuScope by the AQ44 Australian Education Investment Fund. The Mesoarchean Akia Terrane in West Greenland contains a detailed magmatic and metamorphic mineral growth record from 3.2 Ga to at least c. 2.5 Ga. This time span makes this region an important case study in the quest to track secular changes in geodynamic style which may ultimately inform on the development of plate tectonics as a globally linked system of lateral rigid plate motions. The common accessory mineral titanite has recently become recognised as a powerful high temperature geochronometer whose chemistry may chart the thermal conditions of its growth. Furthermore, titanite offers the potential to record the time-temperature history of mafic lithologies, which may lack zircon. Although titanite suffers from higher levels of common Pb than many other UPb chronometers, we show how measurement of 207Pb/206Pb in texturally coeval biotite may assist in the characterization of the appropriate common Pb composition in titanite. Titanite extracted from two samples of mafic gneisses from the Akia Terrane both yield UPb ages of c. 2.54 Ga. Although coeval, their chemistry implies growth under two distinctly different processes. In one case, the titanite has elevated total REE, high Th/U and grew from an in-situ partial melt, consistent with an identical date to granite dyke zircon. In contrast, the second titanite sample contains greater common Pb, lower total REE, lower Th/U, and grew from dominantly hydrothermal fluids. Zr-in-titanite thermometry for partial melt-derived titanite, with activities constrained by phase equilibrium modelling, indicates maxima of c. 690 °C. Elsewhere in the Akia Terrane, coeval metamorphism linked to growth of hydrothermal titanite is estimated at temperatures of c. 670 °C. These new results when coupled with existing findings indicate punctuated, repeated metamorphic ...